Legitimação da arte no campo científico: estudos de caso com grupos de pesquisa do CNPq - Santos, Rojanira Roque dos (Universidade Federal de São Carlos, 2014)
Science and art belong to different social contexts and perform specific functions, however in order to become discipline and knowledge area, the art is dividing the same space with science: the academy. This approach is not free of conflicts since, according to sociologist Pierre Bourdieu, academic space can be considered a social field in this case, scientific field permeated by constant bickering and fights geared to the accumulation of symbolic capital and subsequent conquest of positions domain. Through this scenario, the participants of the field shall develop specific actions focused at the achievement and improvement of their position. Thus, the present study aimed to investigate how the students related to art have articulated their actions in order to conquer positions in the scientific field, based on the following question: what are the strategies of legitimation of art as a discipline and field of knowledge institutionalized in the academy? The research was based on the characteristic theoretical constructs of Social Studies of Science and Technology, essentially the notion of scientific field created by Bourdieu. From the methodological emphasis, we have used a qualitative approach employing such techniques for collect ing data document analysis, interviews and direct observation in a multiple case study with research groups registered at CNPq (Conselho Nacional de Desenvolvimento Científico e Tecnológico). The results indicated that art suffers some degree of resistance to legitimize their actions in the scientific field and this resistance has been faced by academics linked to art through specific actions that, in this study, were considered strategies for the legitimation of art as scientific field, among which mimic the practices of other areas of knowledge, alliances with agents or institutions with dominant positions in the scientific field and participation in research groups.
Keywords: Desenvolvimento da ciência e tecnologia; Campo científico; Conhecimento; Disciplina; Arte; Grupos de pesquisa; Art; Scientific field; Discipline; Area of knowledge; Research groups; OUTROS